Land Use/ Land use zoning Practice at Micro level in Nepal: An Assessment (Voice of Teacher, 2023)
The land use zoning is thought to be better for the sustainable use of land resources utilization in Nepal. Land use (LU) denotes the human activity associated with a specific piece of land and mainly refers to the use by human beings for specific purposes with some sorts of management practices (Khanal, 2000). Specially, Land use is affecting by various factors like, physiographic, topographic, climatic, lithology, soil types, climate, rainfall pattern, cultural and traditional practices as well as socio economic factors etc. With varying physiography conditions around Punchapuri Municipality the land use zones have been found to be a varying shapes and thickness. With the growth of population Punchapuri has expanded the cultivable land of the town. The land use in the Municipality is predominantly nonagricultural with forest, shrub, and grass, covering more than 77% of the total area. The Punchapuri Municipality which is located Surkhet district in province no.6 has been choosen as the study area. Land use map was prepared based on 0.5 m spatial resolution satellite imagery. Various other vector raster and imagery datasets were used ancillary data which enhanced interpretation and classification of land use classes. Information on the losses, damage and its future risk were collected through focus group discussion, key informants, interview, observation and measurement. The paper further emphasizes on a detail study of land use pattern, land system, land forms type, and land capability, geology and natural hazards in order to formulate a classification scheme for land use zoning. This study will certainly help the concerned authorities for the ongoing practices on the land, and land use zoning the finite resource of the country. It will further help to develop plan for the local areas and implement accordingly. Therefore, this study can be regarded as milestone for the planners and development working agencies within the area.